A Influência do modelo de gestão de polícia comunitária-interativa na democratização da Polícia Militar do ES, na cidade de Vitória, entre 1994 e 2006 - Pimentel, Gelson Lozer (2008)
This dissertation has as goal to verify how a transformation from a management model named as traditional policing to a communitary-interactive model has occurred. We searched to show the differences between a traditional policing from a communitary-inter